ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TENTANG PEMBAGIAN HAK WARIS ANAK YANG LAHIR DARI PERKAWINAN SIRI - Dea Rusianda Naibaho; Ni Luh Wayan Yasmiati; Ratna Artha Windari (INTELIGENSIA MEDIA, 2025)
This research aims to (1) examine or analyze the position of children resulting from unregistered marriages in political law in Indonesia, (2) examine or analyze the legal consequences of the inheritance rights of children born from unregistered marriages based on the Constitutional Court Decision Number 46/PUU-VIII/2010. The type of research used is normative legal research by taking a statute approach and a case approach. The results obtained indicate (1) unregistered marriages are not recognized as legitimate children according to the law. However, the status of the child can change to legitimate if the parents submit a marriage confirmation to the religious court. The Constitutional Court Decision confirms the position of children from unregistered and legitimate marriages. (2) The legal consequences for illegitimate children after the Constitutional Court Decision Number 46/PUU- VIII/2010 are: Recognition of civil relations with biological fathers, inheritance rights equal to legitimate children, protection of civil rights of illegitimate children, and the impact on the practice of unregistered marriages.